OP37 A feasibility study of a physical activity intervention designed by and for women aged >55 years in a Bingo club. (13th September 2016) - Evans, JMM; Connelly, J; Jepson, R; Gray, C; Shepherd, A; Mackison, D
Abstract : Background: In 2013, we used participatory methods in a Bingo club in central Scotland (focus groups, questionnaires, workshop) to design a physical activity (PA) intervention for women aged >55 years living in areas of high deprivation. The aim of this phase was to test the feasibility of delivering the intervention in the club, while continuing with a high level of public involvement. Methods: Bingo players were recruited in the club over a 2-week period in April 2015. The target was to recruit 20 women aged >55 years for baseline measures. The club allowed use of their hall 3 days/week from 10–11 am before Bingo games started. A led group exercise session (chair-based exercise, dancercise and line-dancing) lasted 20–35 minutes, with time for discussion/refreshments afterwards. The trained instructors delivered pre-defined intervention messages each week. 35 sessions were delivered in the 12-week intervention period, and attendance data collected. Accelerometers were given to 15 women to wear for a 1-week period at baseline and after intervention delivery. The primary outcome measure was daily time spent in PA. Questionnaires were also administered (knowledge of guidelines, measures of self-efficacy and social support for PA, outcome expectations and physical enjoyment for exercise). In-depth interviews were conducted with all participants and instructors after 12 weeks. Results: 24 women expressed interest; 15 then attended for informed consent/baseline measures. A further six were recruited by word-of-mouth later on. Of these 21 recruits, three provided baseline data but attended no sessions, despite being asked to attend at least 1/week. Age ranged from 55–92 years. SIMD score was available for 16; 12 came from SIMDs 1–3 (most deprived). The women designed their own attendance strategy and there was high retention/engagement. Only 3/15 women showed low engagement with the intervention; the rest all attended least 60% of intended sessions. Qualitative evaluation confirmed the importance of the social element, the habitual nature of Bingo attendance and the suitability of the Bingo club for the intervention. There were improvements in well-being and self-efficacy for PA among women over the 12 weeks, but no clear differences in PA levels in the short-term. Conclusion: It is feasible to deliver a PA intervention in a Bingo club. The intervention had high retention and produced discernible improvements in well-being and self-efficacy among participants, most of whom came from areas of high deprivation. The 12-week intervention has run for a further two rounds due to demand; with the third cycle funded by NHS Forth Valley Health Promotion Service.